Establishing the Level of BIM implementation - A Case Study in Melaka, Malaysia - Yahya Al-Ashmori, Y. (Institute of Physics Publishing, 2019)
The implementation of Building Information Modelling (BIM) in Malaysian construction industry is considered very challenging. Although there is significant support from the government to enhance BIM adoption, the implementation of BIM is still in a very low level. Therefore, this paper is evaluating the level of BIM use among Malaysian construction companies. The research is based on a survey and observation conducted in the state of Melaka in which 90 Malaysian companies were surveyed. Based on the evaluation of 90 construction companies, 63 questionnaires were returned and only 46 were valid for further analysis which covered the main objectives of this research. Result revealed that there is a significant drawback of BIM implementation among construction companies due to the lack of awareness of application process and technology concept. The main factor responsible for the lack of awareness was found to be the delay of organizations to use BIM on their project practices. Hence, it is recommended that organizations should be practicing the BIM process within their company. Also, organizations should have the initiative to develop their roadmap for implementation and development of individual transformation plan that gradually overcomes challenges. Â© Published under licence by IOP Publishing Ltd.